Improving the Generation Z’s Self-Esteem and Decreasing their Mental Issues by Creative Expression Art Therapy - Anggawijayanto, Erydani; Putrikita, Katrim Alifa; Widanarti, Mulianti (Journal of Educational, Health and Community Psychology, 2024)
This research focuses on adolescents with mental health issues such as stress and anxiety. Stress is described as general daily pressure that affects daily behavior, while anxiety is defined as excessive worry about future events. Both stress and anxiety are closely associated with low self-esteem, which refers to an individual's perception and evaluation of their ability to face and solve problems. Various interventions can enhance self-esteem, with art therapy being particularly effective for adolescents. In this study, the State Self-Esteem Scale (SSES) was used to measure self-esteem, and the DASS-21 was used to assess stress, anxiety, and depression symptoms. Five female participants completed the intervention, which consisted of eight sessions conducted over five days. This research utilized a quasi-experimental pre- and post-test method. The intervention results showed a significant increase in global self-esteem scores, as well as changes in stress, anxiety, and depression levels